Preparation of nano-copper glass antibacterial material and application of nano-copper glass antibacterial material in tobacco essence
By applying nano-copper-loaded glass antibacterial materials in tobacco flavors, the problem of fragrances being susceptible to microbial contamination is solved, and long-term sterilization and quality stability are improved.
Patent Information
- Application Number
- CN202411706558.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-11
AI Technical Summary
Flavors and flavors for tobacco are susceptible to microbial contamination, affecting product quality stability, and an effective antibacterial material is needed to solve this problem.
An antibacterial material loaded on glass material is prepared by mixing silica and nanocopper-loaded diatomaceous earth material in a specific proportion and forming it into spherical particles in a granulator.
It achieves a long-term sterilization effect, is cheap and biosafe, and can effectively prevent microbial contamination of tobacco flavors and fragrances, and improve product quality stability.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tobacco flavors and fragrances, and in particular to the preparation of a nano copper glass antibacterial material and the application of the nano copper glass antibacterial material in tobacco flavors. Background Art
[0002] When traditional tobacco products are used, they release mixed smoke containing thousands of compounds, which not only contain a variety of volatile flavor components, but also harmful substances such as tar, nicotine and carbon monoxide, which seriously endanger people's health. Therefore, the "tar reduction and harm reduction" policy came into being. The implementation of this policy inevitably led to a serious decline in the taste and comfort of tobacco products. Tobacco flavors and fragrances have the functions of enriching tobacco aroma, improving smoking quality, and improving tobacco leaf quality. They are important materials for improving the physical and chemical properties and taste of products. They have become an indispensable additive for tobacco products, making up for the shortcomings of the "tar reduction and harm reduction" policy. At the same time, tobacco flavors and fragrances are also related to the composition of the characteristic flavor of cigarette brands.
[0003] The quality stability of tobacco flavors and fragrances determines the quality stability of cigarette products and has received extensive attention from tobacco industry manufacturers. Among them, microbial indicators are one of the important factors affecting the quality stability of tobacco flavors and fragrances, and are also an important indicator for evaluating the sanitary status of tobacco flavors and fragrances. Since tobacco flavors and fragrances are of various types and complex components, rich in nutrients required for microbial growth, they are easily contaminated and deteriorated. Therefore, it is necessary to carry out antibacterial treatment on tobacco flavors and fragrances.
[0004] Commonly used antimicrobial agents are generally divided into inorganic antimicrobial agents, organic antimicrobial agents and natural antimicrobial agents. Among them, inorganic antimicrobial agents use the antimicrobial ability of metals such as silver, copper, and zinc, and have the advantages of broad-spectrum antimicrobial, high temperature resistance, strong durability, and excellent biocompatibility. Metal nanoparticles have higher antimicrobial activity and have significant advantages such as not easy to develop drug resistance, non-toxic or low toxicity, and heat resistance. Copper is a trace element necessary for human life. Compared with other metal nanomaterials, nano-copper has the advantages of strong antibacterial properties, low cost, and high biosafety. Nano-copper antibacterial materials with glass as the carrier can have long-term antibacterial effects during use, and have the advantages of low price and low cost. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a preparation method of a nano-copper glass antibacterial material and its application in tobacco flavors. Aiming at the risk of microbial contamination during the use of tobacco flavors and fragrances, which leads to adverse factors affecting the stability of product quality, the present invention uses nano-copper as a bactericidal source and loads it on a glass material, and it is expected to obtain an antibacterial material that can achieve long-term bactericidal effect and is low in price.
[0006] The technical problem to be solved by the present invention is achieved through the following technical solutions:
[0007] A nano copper glass antibacterial material comprises silicon dioxide and a diatomaceous earth material loaded with nano copper, wherein the mass ratio of the silicon dioxide and the diatomaceous earth material loaded with nano copper is (60-80):(20-40). The nano copper glass antibacterial material is prepared by fully and evenly grinding the silicon dioxide and the diatomaceous earth material loaded with nano copper and then forming the grinding particles into spherical particles in a granulator.
[0008] Preferably, in the above technical solution, the pressure of the granulator is 35-45Mpa and maintained for 10-20min.
[0009] A method for preparing a nano copper glass antibacterial material comprises the following steps:
[0010] (1) Preparation of copper-containing sol: tetraethoxysilane and ethanol are mixed in a volume ratio of 1:5, stirred for at least 0.5 h, and then a copper chloride hydrochloric acid solution is gradually added dropwise to the mixture, and stirred for at least 1 h to obtain the copper-containing sol;
[0011] (2) Preparation of diatomite material loaded with nano-copper: diatomite is mixed with the copper-containing sol obtained in step (1) and soaked for 30-60 minutes, dried for 2-4 hours, and then heated to 400° C. in a heating device and calcined for 1.5-3 hours, and then heated to 600° C. in a nitrogen-hydrogen mixed gas environment and calcined for 1-2 hours to obtain a diatomite material loaded with nano-copper;
[0012] (3) Preparation of nano-copper glass antibacterial material: The pretreated silica and the nano-copper loaded diatomaceous earth material obtained in step (2) are mixed in a mass ratio of (60-80): (20-40), fully ground and then formed into spherical particles in a granulator at a pressure of 35-45 MPa for a holding time of 10-20 minutes.
[0013] Preferably, in the above technical solution, in step (1), the ethanol concentration is above 90%; the concentration of the cupric chloride solution is 30-55wt%, and the concentration of the hydrochloric acid is 0.2-0.6mol / L; and the volume ratio of the cupric chloride hydrochloric acid solution to tetraethoxysilane is 1:2-6.
[0014] Preferably, in the above technical solution, in step (2), the mass ratio of diatomaceous earth to copper-containing sol is 1:3-9, and the volume ratio of nitrogen to hydrogen in the nitrogen-hydrogen mixed gas is 4:1.
[0015] Preferably, in the above technical solution, in step (3), the pretreatment of the silicon dioxide comprises: grinding the silicon dioxide in a ball mill and sieving the silicon dioxide, wherein the aperture of the sieve used for sieving is 75 μm.
[0016] Preferably, in the above technical solution, in step (3), the pretreatment specifically comprises: adding 1 part of silicon dioxide and 3 parts of deionized water into a ball mill by weight, with the speed of the ball mill being 400-550 r / min for 1-2 hours.
[0017] Preferably, in the above technical solution, in step (3), the granulator pressure is 35-45Mpa and maintained for 10-20min.
[0018] The invention discloses an application of a nano copper glass antibacterial material in the sterilization of tobacco flavors and fragrances. The nano copper glass antibacterial material is a nano copper glass antibacterial material prepared according to the above preparation method.
[0019] A nano copper glass antibacterial material is used in the sterilization of tobacco flavors and fragrances. The application is as follows: according to the preparation process of finished tobacco flavors and fragrances, after the product formula is prepared, the tobacco flavors and fragrances need to be transferred into a turnover tank, stirred and mixed evenly, and then transferred to a packaging barrel; sterilization tanks are respectively installed at the inlet and outlet of the turnover tank, and 1 / 4 volume of the nano copper glass antibacterial material is transferred into the sterilization tank.
[0020] The above technical solution of the present invention has the following beneficial effects:
[0021] In the present invention, nano copper is loaded on the surface of silica, nano copper is used as an antibacterial source, and silica fiber is used as the base material of the antibacterial material, which has the advantages of long-lasting antibacterial effect and biosafety. At the same time, it can kill bacteria for a long time, is low in price and can be used in multiple scenarios. Moreover, tobacco extract is used in the preparation of nano copper, and the synthesis process is green and environmentally friendly. DETAILED DESCRIPTION
[0022] Various exemplary embodiments of the present invention will now be described in detail. It should be noted that the relative arrangement of components and steps, numerical expressions and numerical values set forth in these embodiments do not limit the scope of the present invention unless specifically stated otherwise.
[0023] Unless otherwise specified, the reagents used in this application are all commercially available or obtained through commercial channels, or can be prepared by referring to existing chemical methods.
[0024] Example 1
[0025] (1) Preparation of nano copper glass antibacterial materials:
[0026] 1 part of tetraethoxysilane is mixed with 5 parts of ethanol by volume, stirred for more than 0.5h, and then cupric chloride hydrochloric acid solution is gradually added dropwise to the mixture of tetraethoxysilane and ethanol, the volume ratio of cupric chloride hydrochloric acid solution to tetraethoxysilane is 1:2, and stirred for more than 1h to obtain a copper-containing sol. The ethanol concentration is more than 90%. The concentration of the cupric chloride solution is 30-55wt%, and the concentration of the hydrochloric acid is 0.2-0.6mol / L.
[0027] The diatomite and the copper-containing sol were mixed and soaked for 30 minutes, the mass ratio of diatomite to the copper-containing sol was 1:3, and then dried for 2 hours. In a heating device, the temperature was raised to 400°C and calcined for 1.5 hours, and then in a nitrogen (80%)-hydrogen (20%) mixed gas environment, the temperature was raised to 600°C and calcined for 1 hour to obtain a diatomite material loaded with nano-copper.
[0028] According to weight, 60 parts of the silicon dioxide and 40 parts of the diatomaceous earth material loaded with nano-copper were fully ground and added into a granulator. The pressure used in the granulator was 35 MPa and the maintenance time was 10 minutes.
[0029] (2) Antibacterial treatment of finished tobacco flavors and fragrances:
[0030] After the formula of the finished golden leaf (hard silver) flavor and fragrance product is prepared (provided by Henan China Tobacco Zhumadian Cigarette Factory), the tobacco flavor and fragrance needs to be transferred into the turnover tank, stirred and mixed evenly before being transferred to the packaging barrel.
[0031] Sterilization tanks were installed at the inlet and outlet of the turnover tanks, and 1 / 4 volume of nano copper glass antibacterial material was transferred into the sterilization tanks. The finished tobacco flavors and fragrances after filtration and sterilization were tested for antibacterial properties, and the results are shown in Table 1.
[0032] (3) Recycling of antibacterial materials:
[0033] The nano copper glass antibacterial material in the sterilization tank is filtered and recovered regularly, ultrasonically cleaned with water, ethanol and propylene glycol for 20-30 minutes respectively, and can be used again after drying.
[0034] Table 1 Antibacterial test results
[0035]
[0036] Example 2
[0037] (1) Preparation of nano copper glass antibacterial materials:
[0038] 1 part of tetraethoxysilane is mixed with 5 parts of ethanol by volume, stirred for more than 0.5h, and then cupric chloride hydrochloric acid solution is gradually added dropwise to the mixture of tetraethoxysilane and ethanol, the volume ratio of cupric chloride hydrochloric acid solution to tetraethoxysilane is 1:3.5, and stirred for more than 1h to obtain a copper-containing sol. The ethanol concentration is more than 90%. The concentration of the cupric chloride solution is 30-55wt%, and the concentration of the hydrochloric acid is 0.2-0.6mol / L.
[0039] The diatomite and the copper-containing sol were mixed and soaked for 60 minutes, the mass ratio of diatomite to copper-containing sol was 1:4.5, and then dried for 4 hours. In a heating device, the temperature was raised to 400°C and calcined for 3 hours, and then in a nitrogen (80%)-hydrogen (20%) mixed gas environment, the temperature was raised to 600°C and calcined for 2 hours to obtain a diatomite material loaded with nano-copper.
[0040] According to weight, 80 parts of the silicon dioxide and 20 parts of the diatomaceous earth material loaded with nano-copper were fully ground and added into a granulator. The pressure used in the granulator was 45 MPa and the maintenance time was 20 minutes.
[0041] (2) Antibacterial treatment of finished tobacco flavors and fragrances:
[0042] According to the blending process of finished tobacco flavors and fragrances, after the product formula is completed, the tobacco flavors and fragrances need to be transferred to turnover tanks, stirred and mixed evenly before being transferred to packaging barrels.
[0043] Sterilization tanks were installed at the inlet and outlet of the turnover tanks, and 1 / 4 volume of nano copper glass antibacterial material was transferred into the sterilization tanks. The finished tobacco flavors and fragrances after filtration and sterilization were tested for antibacterial properties, and the results are shown in Table 2.
[0044] The above tobacco flavors and fragrances are the same as those in Example 1. Of course, the present application is not limited thereto, and common products in the art may also be used instead.
[0045] (3) Recycling of antibacterial materials:
[0046] The nano copper glass antibacterial material in the sterilization tank is filtered and recovered regularly, ultrasonically cleaned with water, ethanol and propylene glycol for 20-30 minutes respectively, and can be used again after drying.
[0047] Table 2 Antibacterial test results
[0048]
[0049] Example 3
[0050] (1) Preparation of nano copper glass antibacterial materials:
[0051] 1 part of tetraethoxysilane is mixed with 5 parts of ethanol by volume, stirred for more than 0.5h, and then cupric chloride hydrochloric acid solution is gradually added dropwise to the mixture of tetraethoxysilane and ethanol, the volume ratio of cupric chloride hydrochloric acid solution to tetraethoxysilane is 1:4, and stirred for more than 1h to obtain a copper-containing sol. The ethanol concentration is more than 90%. The concentration of the cupric chloride solution is 30-55wt%, and the concentration of the hydrochloric acid is 0.2-0.6mol / L.
[0052] The diatomite and the copper-containing sol were mixed and soaked for 40 minutes, the mass ratio of diatomite to the copper-containing sol was 1:6, and then dried for 2.5 hours. In a heating device, the temperature was raised to 400°C and calcined for 2 hours, and then in a nitrogen (80%)-hydrogen (20%) mixed gas environment, the temperature was raised to 600°C and calcined for 1.3 hours to obtain a diatomite material loaded with nano-copper.
[0053] According to weight, 65 parts of the silicon dioxide and 35 parts of the diatomaceous earth material loaded with nano-copper were fully ground and added into a granulator. The pressure used in the granulator was 38 MPa and the maintenance time was 14 minutes.
[0054] (2) Antibacterial treatment of finished tobacco flavors and fragrances:
[0055] According to the blending process of finished tobacco flavors and fragrances, after the product formula is completed, the tobacco flavors and fragrances need to be transferred to turnover tanks, stirred and mixed evenly before being transferred to packaging barrels.
[0056] Sterilization tanks were installed at the inlet and outlet of the turnover tanks, and 1 / 4 volume of nano copper glass antibacterial material was transferred into the sterilization tanks. The finished tobacco flavors and fragrances after filtration and sterilization were tested for antibacterial properties, and the results are shown in Table 3.
[0057] The above tobacco flavors and fragrances are the same as those in Example 1. Of course, the present application is not limited thereto, and common products in the art may also be used instead.
[0058] (3) Recycling of antibacterial materials:
[0059] The nano copper glass antibacterial material in the sterilization tank is filtered and recovered regularly, ultrasonically cleaned with water, ethanol and propylene glycol for 20-30 minutes respectively, and can be used again after drying.
[0060] Table 3 Antibacterial test results
[0061]
[0062] Example 4
[0063] (1) Preparation of nano copper glass antibacterial materials:
[0064] Calculated by volume, 1 part of tetraethoxysilane is mixed with 5 parts of ethanol and stirred for more than 0.5h. Then, a hydrochloric acid solution of cupric chloride is gradually added dropwise to the mixture of tetraethoxysilane and ethanol. The volume ratio of the hydrochloric acid solution of cupric chloride to tetraethoxysilane is 1:6. Stirring is continued for more than 1h to obtain a copper-containing sol.
[0065] The diatomite and the copper-containing sol were mixed and soaked for 50 minutes, the mass ratio of diatomite to copper-containing sol was 1:9, and then dried for 3.5 hours. In a heating device, the temperature was raised to 400°C and calcined for 2.5 hours, and then in a nitrogen (80%)-hydrogen (20%) mixed gas environment, the temperature was raised to 600°C and calcined for 1.6 hours to obtain a diatomite material loaded with nano-copper.
[0066] According to weight, 75 parts of the silicon dioxide and 25 parts of the diatomaceous earth material loaded with nano-copper were fully ground and added into a granulator. The pressure used in the granulator was 42 MPa and the maintenance time was 17 minutes.
[0067] (2) Antibacterial treatment of finished tobacco flavors and fragrances:
[0068] According to the blending process of finished tobacco flavors and fragrances, after the product formula is completed, the tobacco flavors and fragrances need to be transferred to turnover tanks, stirred and mixed evenly before being transferred to packaging barrels.
[0069] Sterilization tanks were installed at the inlet and outlet of the turnover tanks, and 1 / 4 volume of nano copper glass antibacterial material was transferred into the sterilization tanks. The finished tobacco flavors and fragrances after filtration and sterilization were tested for antibacterial properties, and the results are shown in Table 4.
[0070] The above tobacco flavors and fragrances are the same as those in Example 1. Of course, the present application is not limited thereto, and common products in the art may also be used instead.
[0071] (3) Recycling of antibacterial materials:
[0072] The nano copper glass antibacterial material in the sterilization tank is filtered and recovered regularly, ultrasonically cleaned with water, ethanol and propylene glycol for 20-30 minutes respectively, and can be used again after drying.
[0073] Table 4 Antibacterial test results
[0074]
[0075]
[0076] Although the present invention has been disclosed as above by the embodiments, it is not intended to limit the present invention. Any person skilled in the art may make various choices and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention is limited by the claims and their equivalents.
Claims
1. A nano copper glass antibacterial material, characterized in that: The nano-copper glass antibacterial material comprises silicon dioxide and diatomaceous earth material loaded with nano-copper, and the mass ratio of the two is (60-80): (20-40). The nano-copper glass antibacterial material is prepared by fully and evenly grinding the silicon dioxide and the diatomaceous earth material loaded with nano-copper and then forming them into spherical particles in a granulator.
2. The nano copper glass antibacterial material according to claim 1, characterized in that: The granulator pressure is 35-45Mpa and maintained for 10-20min.
3. A method for preparing a nano copper glass antibacterial material, characterized in that: The following steps are involved: (1) Preparation of copper-containing sol: tetraethoxysilane and ethanol are mixed in a volume ratio of 1:5, stirred for at least 0.5 h, and then a copper chloride hydrochloric acid solution is gradually added dropwise to the mixture, and stirred for at least 1 h to obtain the copper-containing sol; (2) Preparation of diatomite material loaded with nano-copper: diatomite is mixed with the copper-containing sol obtained in step (1) and soaked for 30-60 minutes, dried for 2-4 hours, and then heated to 400° C. in a heating device and calcined for 1.5-3 hours, and then heated to 600° C. in a nitrogen-hydrogen mixed gas environment and calcined for 1-2 hours to obtain a diatomite material loaded with nano-copper; (3) Preparation of nano-copper glass antibacterial material: The pretreated silica and the nano-copper loaded diatomaceous earth material obtained in step (2) are mixed in a mass ratio of (60-80): (20-40), fully ground and then formed into spherical particles in a granulator at a pressure of 35-45 MPa for a holding time of 10-20 minutes.
4. The method for preparing the nano copper glass antibacterial material according to claim 3, characterized in that: In step (1), the concentration of ethanol is above 90%; the concentration of the cupric chloride solution is 30-55wt%, the concentration of hydrochloric acid is 0.2-0.6mol / L; and the volume ratio of the cupric chloride hydrochloric acid solution to tetraethoxysilane is 1:2-6.
5. The method for preparing the nano copper glass antibacterial material according to claim 3, characterized in that: In step (2), the mass ratio of diatomaceous earth to copper-containing sol is 1:3-9, and the volume ratio of nitrogen to hydrogen in the nitrogen-hydrogen mixed gas is 4:
1.
6. The method for preparing the nano copper glass antibacterial material according to claim 3, characterized in that: In step (3), the pretreatment of silicon dioxide comprises: grinding the silicon dioxide in a ball mill and sieving the silicon dioxide, wherein the sieve used for sieving has an aperture of 75 μm.
7. The method for preparing the nano copper glass antibacterial material according to claim 6, characterized in that: In step (3), the pretreatment specifically includes: adding 1 part of silicon dioxide and 3 parts of deionized water into a ball mill by weight, with the speed of the ball mill being 400-550 r / min for 1-2 hours.
8. The method for preparing the nano copper glass antibacterial material according to claim 3, characterized in that: In step (3), the granulator pressure is 35-45Mpa and maintained for 10-20min.
9. Application of nano copper glass antibacterial material in the sterilization of tobacco flavors and fragrances, characterized in that: The nano copper glass antibacterial material is a nano copper glass antibacterial material prepared according to any one of the preparation methods described in claims 3-8.
10. Application of nano copper glass antibacterial material in the sterilization of tobacco flavors and fragrances, characterized in that: The application is as follows: according to the blending process of finished tobacco flavors and fragrances, after the product formula is completed, the tobacco flavors and fragrances need to be transferred into a turnover tank, stirred and mixed evenly, and then transferred to a packaging barrel; a sterilization tank is installed at the inlet and outlet of the turnover tank, and 1 / 4 volume of nano-copper glass antibacterial material is transferred into the sterilization tank.